Inflammatory role of microglia in brain injury caused by subarachnoid hemorrhage - Wang, Xiao-Yi; Wu, Fan; Zhan, Ren-Ya; Zhou, Heng-Jun (Frontiers in Cellular Neuroscience, 2022)
Early brain injury is a series of pathophysiological changes and direct damage of brain tissue within 72 hours after subarachnoid hemorrhage before cerebral vasospasm occurs. Early brain injury is a key factor affecting the prognosis of subarachnoid hemorrhage, and its possible pathological mechanisms include oxidative stress, cell apoptosis, autophagy, and immune inflammation. Microglia are important immune cells of the central nervous system. Microglia play a dual role of protection and injury. Microglia are involved in the occurrence of brain edema, the processes of neuronal apoptosis, and blood-brain barrier disruption after SAH through the signaling pathways mediated by receptors such as Toll-like receptor 4 (TLR4), calcium-sensing receptor (CaSR), and triggering receptor expressed on myeloid cells 1 (TREM-1), which secrete anti-inflammatory cytokines like interleukins and tumor necrosis factor α. Conversely, they exert their anti-inflammatory and protective effects by expressing substances such as neuroglobin and heme oxygenase-1. This article reviews the latest developments in single-cell transcriptomics for microglia in early brain injury after subarachnoid hemorrhage and its inflammatory role.